Virtual environment for sustainable housing development: exploring satisfaction and enjoyment in immersive visualization/ Athira Azmi ... [et al.] - Azmi, Athira; Ibrahim, Rahinah; Abd Ghafar, Maszura; Rashidi, Ali (Universiti Teknologi MARA, Perak, 2023)
One of the objectives of sustainable development is to create a world of interconnected spaces that incorporates smart technologies such as virtual reality (VR) in every phase. This includes the use of virtual environment to replace physically built show units for sell-then-built housing development. With this vision, it is vital to evaluate how the virtual environment impacted satisfaction and perceived enjoyment, which are the two key predictors of purchase intention. This paper hypothesized on the relationships between the atmosphere, satisfaction, and perceived enjoyment in the virtual environment with purchase intention. An experiment with 60 real potential homebuyers was conducted to test the hypotheses. Results analyzed using paired samples t-test indicate that the atmosphere, satisfaction, perceived enjoyment, and purchase intention is statistically different (p < 0.05) in the physical and the virtual environment, while the PLS-SEM analysis revealed that the atmosphere in virtual environment positively effect satisfaction and perceived enjoyment, which subsequently positively effect purchase intention. The results presented in this paper would lead towards an enhanced development using virtual reality in smart cities that incorporates intelligence in human-computer interactions and consumer experience. This study extends the theory of consumer behaviour in architecture design for a smarter design that incorporates human emotions and behaviour in decision-making.